Kohesivitas Tim dan Sikap terhadap Kepemimpinan Wasit sebagai Prediktor Kecenderungan Perilaku Agresif Pemain Sepakbola - Amin Akbar; Thomas Dicky Hastjarjo (Faculty of Psychology, Universitas Gadjah Mada, 2018)
This study aimed to determine the role of team cohesiveness and attitude toward referee leadership to the aggressiveness tendency in Indonesian professional football player. Participants in this research were 90 Indonesian professional football players. The data were collected using three instruments: aggressiveness behavioral tendencies scale, team cohesiveness scale, and attitude toward referee leadership scale. Data were analyzed using linear regression analysis in SPSS 20. Findings from this research were the team cohesiveness and the attitude towards referee leadership have contributed in aggressive behavioral tendencies of Indonesian professional football player, shown by the value of R = 0.509 and R square = 0.259; p <0.01. Team cohesiveness and the attitude toward referee leadership effectively contributed as much as 25.9% on the aggressiveness tendency among Indonesia professional football players.